Biliary Adenofibroma with Carcinoma In Situ: A Rare Case Report - N. Thao T. Nguyen; Theresa R. Harring; Laurie Holley; John A. Goss; Christine A. O’Mahony (Case Reports in Hepatology)
This case report exhibits a rare biliary tumor within the liver of a 53-year-old Caucasian woman. This exophytic, multicystic, 6.5 × 5.0 cm mass was composed of complex tubulocystic structures lined by nonmucin-secreting, biliary epithelium embedded in fibrous stroma, consistent with biliary adenofibroma. This is the seventh case described in the literature. Multiple foci of high-grade dysplasia/carcinoma in situ were found with a microscopic focus of invasive carcinoma in review of the pathology, making this only the second case reporting malignant transformation. It is presented to illustrate the premalignant potential in a biliary epithelial tumor currently categorized as benign.